LOOKING AT THE LINK BETWEEN STUDENTS’ SPEAKING ANXIETY AND SPEAKING ACHIEVEMENT - Lenny Marzulina; Beni Wijaya; Hilma Suryani; Nurul Aryanti; Tania Janesa Utami (Universitas Jambi, 2018)
The objective of this study is to find out the link between speaking anxiety and speaking achievement of the eighth grade students of SMP Negeri 03 Palembang. The method used was correlational study. The data were collected by using questionnaire of speaking anxiety and speaking test of speaking achievement. One hundred seventeen students were involved in the study and the data were analyzed by test analysis. The result showed that 3,4% students had high anxiety, 68,3% students had medium anxiety, and 28,2% students had low anxiety. Besides that, the result also showed 5,1% students had very good speaking achievement, 59,8% students had good speaking achievement, 32,4% students had fair speaking achievement and 2,5% students had poor speaking achievement. There was no link between speaking anxiety and their speaking achievement since the correlation coefficient or r- obtained (-0.167) was lower that r-table (0.1816), and p-output (0.071) higher than (0.05).